Design of a dual-band antenna for energy harvesting application - Maizatul Alice Meor Said; Syed Mohd Iqwan Naqiuddin Syed Jaya; Zahriladha Zakaria; Mohamad Harris Misran; Mohd Muzafar Ismail (Institute of Advanced Engineering and Science, 2021)
This report presents an investigation on how to improve the current dual-band antenna to enhance the better result of the antenna parameters for energy harvesting application. Besides that, to develop a new design and validate the antenna frequencies that will operate at 2.4 GHz and 5.4 GHz. At 5.4 GHz, more data can be transmitted compare to 2.4 GHz. However, 2.4 GHz has long distance of radiation, so it can be used when far away from the antenna module compare to 5 GHz that has short distance in radiation. The development of this project includes the scope of designing and testing of antenna using computer simulation technology (CST) 2018 software and vector network analyzer (VNA) equipment. In the process of designing, fundamental parameters of antenna are being measured and validated, in purpose to identify the better antenna performance.